Implications of the local haemodynamic forces on the phenotype of coronary plaques. Issue 14 (15th March 2019) - Bourantas, Christos V; Zanchin, Thomas; Sakellarios, Antonis; Karagiannis, Alexios; Ramasamy, Anantharaman; Yamaji, Kyohei; Taniwaki, Masanori; Heg, Dik; Moschovitis, Aris; Fotiadis, Dimitrios; Mihalis, Lampros; Baumbach, Andreas; et al.
Abstract : Aim: To examine the effect of endothelial shear stress (ESS) on the dynamic changes in plaque phenotype. Methods: Patients with myocardial infarction that had intravascular ultrasound-virtual histology (IVUS-VH) and optical coherence tomography (OCT) at baseline and 13-month follow-up were studied. The IVUS-VH data were used to reconstruct the nonculprit vessels, and in the obtained models the ESS was estimated in 3 mm segments. Plaque morphology was derived in each segment from IVUS-VH and OCT. Disease progression was defined as the presence of ≥2 out of the following criteria: reduction in lumen area, increase in plaque burden and change of plaque morphology to a more vulnerable phenotype. Linear mixed effects models were used to assess the effect of ESS in different phenotypes. Results: Sixty-eight vessels were included in the analysis. Low ESS was associated with plaque progression in all phenotypes. The effect of ESS on plaque burden (p for interaction=0.467) and phenotype (p for interaction=0.188) was similar in all plaque types, whereas the effect of ESS on the changes in lumen dimensions was more prominent in disease-free (β=0.70, p<0.001) than fibrotic/fibrocalcific (β=0.28, p<0.001) or lipid-rich plaques (β=0.15, p=0.015). Standalone IVUS-VH misclassified plaque morphology in one-third of the cases leading to erroneous estimations about the effect of ESS on plaque evolution in different phenotypes. Conclusions: The effect of ESS on plaque progression is similar in all phenotypes and cannot be accurately assessed by standalone IVUS-VH which often misclassifies plaque morphology. Therefore, multimodality imaging should be considered to examine the implications of ESS on plaque evolution. Clinical trial registration: NCT00962416 ; Post-results.